Peran Guru Dalam Mengembangkan Keterampilan Berdialog Siswa Kelas VII SMP Negeri 7 Kupang Melalui Penggunaan Metode Bermain Peran - Poy, Apliana; Djuli, Labu; Margareta, Karus M. (Jurnal Lazuardi, 2025)
The focus of this research is "How is the role of teachers in developing dialogue skills for grade VII students of SMP Negeri 7 Kupang through the use of role-playing methods. The purpose of this study is to find out and describe the role of teachers in developing dialogue skills of grade VII students of SMP Negeri 7 Kupang through the use of role-playing methods. The theory used is Information Processing Theory, because what is measured in this study is the role of a teacher in developing dialogue skills with students. The method used in this study is qualitative descriptive. In this study, the researcher selected material dialogue skills using a role-playing method in accordance with of the Independent Curriculum found Revition Edition grade VII in the odd semester phase D 7.3.1 Conveying ideas, thoughts, views, directions, or messages for the purpose of proposing, solving problems, and providing solutions orally in the form of monologues and dialogues logically, ,critical, and creatively. The Role-Playing method is a method used in language learning, especially learning dialogue skills. Based on the results of the analysis conducted on only teachers Indonesia Language and 24 students in grades VII-C of SMP Negeri 7 Kupang, the role of teachers in developing dialogue skills of grade VII students of SMP Negeri 7 Kupang through the use of role-playing methods can be said to be ineffective. These results can be seen from the percentage success rate of 64.58% of students who are unable to dialogue using the role-playing method, namely the achievement of scores ranging from 70-100. Students who are said to have completed or exceeded the KKM amounted to 8 people with a percentage of 33.33%, while students who did not complete amounted to 16 people with a percentage of 66.66%.